2015
DOI: 10.1007/s10971-015-3627-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of N-doped anatase–rutile mixed phase TiO2 nanorods assembled microspheres synthesized by simple sol–gel method

Abstract: In this study, N-doped anatase-rutile mixed phase TiO 2 nanorods assembled microspheres were synthesized via a direct and simple sol-gel method. The physical analysis via X-ray diffraction indicated that the prepared sample had a mixed phase of anatase and rutile TiO 2 . The morphology of the structure was observed with field emission scanning electron microscopy, transmission electron microscopy and atomic force microscopy, which showed that the formation of TiO 2 microspheres was constructed by TiO 2 nanorod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The band between 400 and 800 cm −1 were assigned to the strong vibration of Ti-O and Ti-O-Ti species. The peaks at 1346-1417 and 1050-1095 cm −1 could be ascribed to the nitrogen atoms embedded in the TiO2 network [29,30]. These results clearly demonstrated that the nitrogen doped TiO2 has been incorporated into the DLHF structure.…”
Section: Physical Properties Of Dlhf Membranesmentioning
confidence: 70%
“…The band between 400 and 800 cm −1 were assigned to the strong vibration of Ti-O and Ti-O-Ti species. The peaks at 1346-1417 and 1050-1095 cm −1 could be ascribed to the nitrogen atoms embedded in the TiO2 network [29,30]. These results clearly demonstrated that the nitrogen doped TiO2 has been incorporated into the DLHF structure.…”
Section: Physical Properties Of Dlhf Membranesmentioning
confidence: 70%
“…The peaks at 284.2 and 285.2 eV were assigned to (C–C–OH boning) and (O–C–O or C=O bonding) respectively, revealing that the carbon atoms come from cellulose molecules [ 25 ]. Furthermore, the peak at 282.4 eV confirms the existence of C as a dopant in TiO 2 photocatalyst, since the doped carbon in TiO 2 showed a very low C 1s binding energy at 281–282 eV [ 26 ]. Figure 8 c shows the high resolution XPS spectra of O 1s.…”
Section: Resultsmentioning
confidence: 99%
“…When the mixed-phase TiO 2 is formed, the Fermi energies in the boundary between the anatase and rutile phases should be the same. This leads the potential of the conduction band (CB) and valence band (VB) of rutile to lie above those of anatase, which promotes excited electron transfer from anatase to rutile with a lower band energy [ 28 , 29 ]. In turn, the effect enhances charge separation and inhibits charge recombination.…”
Section: Resultsmentioning
confidence: 99%